IN-SERVICE REMEDIATION OF A RAILWAY EMBANKMENT TO PREVENT SETTLEMENT - Jan Grepl (Acta Polytechnica CTU Proceedings, 2019)
After optimization of the railway geometry for higher speed, a continuous settlement of the track occurred. Improvement of the embankment body was needed; however, a complete traffic interruption was not allowed. The reconstruction work has been done using the methods of special ground engineering such as vibro-stone columns and driven ductile piles.